The Influence of Socioeconomic Characteristics on Anthropometry, Nutrition Knowledge, and Attitude of People Living With HIV/AIDS Attending Special Treatment Center (STC) National Hospital Abuja, Nigeria - Okorie, Ijioma; Okorie, Adaeze Christiana (Frontiers in Nutrition, 2022)
The work is on the influence of socioeconomic status of people living with HIV/AIDS (PLWHA) on their anthropometry, nutrition knowledge, and attitude, attending special treatment center (STC) in National Hospital Abuja, Nigeria. A cross-sectional study design was carried out in the STC and a total of two hundred and seventy [270 (150 men and 120 women)] PLWHA were used for the study. The PLWHA attend STC once in 2 months and subjects were grouped into 16 giving 4 groups per week since the center runs Monday through Thursday weekly and by 2 months, there were altogether 32 groups. Socioeconomic characteristics, nutrition knowledge and attitude, and anthropometric data were collected. Data were analyzed using descriptive statistics, chi-square, and regression analysis. The study revealed that 41.1% of PLWHA had poor knowledge of nutrition, 29.1% had both fair and good knowledge while 0.7% had excellent knowledge. A total of 52.8% had a positive attitude toward nutrition. The skinfold status of the respondents showed that 56.0% were malnourished, while their body mass index (BMI) revealed that 49.3% were normal. Gender (being female) and age (being young) had a significant (P < 0.01) influence on the BMI of PLWHA, while being female significantly influenced their skinfold status. Self-employed and being female were strongest (P < 0.01) positive predictors of nutrition knowledge, while low education had a negative influence on their attitude toward nutrition. Good nutrition knowledge, attitude, and improved socioeconomic characteristics are important tools in the care process of PLWHA, for sustainable healthy PLWHA, leading to a healthy society at large.